Transcriptome Profiling Reveals a Novel Mechanism of Antiviral Immunity Upon Sacbrood Virus Infection in Honey Bee Larvae (Apis cerana) - Guo, Yulong; Zhang, Zhengyi; Zhuang, Mingsheng; Wang, Liuhao; Li, Kai; Yao, Jun; Yang, Huipeng; Huang, Jiaxing; Hao, Yue; Ying, Fan; Mannan, Hira; Wu, Jie; et al. (Frontiers in Microbiology, 2021)
The honey bee is one of the most important pollinators in the agricultural system and is responsible for pollinating a third of all food we eat. Sacbrood virus (SBV) is a member of the virus family Iflaviridae and affects honey bee larvae and causes particularly devastating disease in the Asian honey bees, Apis cerana. Chinese Sacbrood virus (CSBV) is a geographic strain of SBV identified in China and has resulted in mass death of honey bees in China in recent years. However, the molecular mechanism underlying SBV infection in the Asian honey bee has remained unelucidated. In this present study, we employed high throughput next-generation sequencing technology to study the host transcriptional responses to CSBV infection in A. cerana larvae, and were able to identify genome-wide differentially expressed genes associated with the viral infection. Our study identified 2534 differentially expressed genes (DEGs) involved in host innate immunity including Toll and immune deficiency (IMD) pathways, RNA interference (RNAi) pathway,endocytosis, etc. Notably, the expression of genes encoding antimicrobial peptides (abaecin, apidaecin, hymenoptaecin, defensin) and core components of RNAi such as Dicer-like and Ago2 were found to be significantly upregulated in CSBV infected larvae. Most importantly, the expression of Sirtuin genes, a family of signaling proteins involved in metabolic regulation, apoptosis, and intracellular signaling was found to be upregulated, providing the first evidence of the involvement of Sirtuin signaling pathway in insects’ immune response to a virus infection. The results obtained from this study provide novel insights into the molecular mechanism and immune responses involved in CSBV infection, which in turn will contribute to the development of diagnostics and treatment for the diseases in honey bees.